Pengaruh Persepsi Keamanan Data,Gaya Hidup, dan Promosi terhadap Minat Menggunakan Dompet Digital pada Generasi Z - A.Muh Fathi Katsirun Nawal; Joan Nathania Latifa; Unaiza Nafta Lima Haka; Icha Agustin Nurhastuti; Ahmad Chafid Alwi (Journal Economic Management and Business, 2025)
The development of digital technology has transformed payment systems from cash to non-cash methods such as digital wallets (e-wallets), which are practical and efficient. Generation Z, as active users of these services, face issues of personal data security, digital lifestyle, and promotional competition from service providers. This study analyzes the influence of perceptions of data security, lifestyle, and promotions on Generation Z's interest in using digital wallets. The method used was a quantitative survey with an online questionnaire on Google Forms in September–October 2025, involving 183 respondents. The results show that promotions, lifestyle, and data security have a positive and significant effect on interest in using digital wallets, with lifestyle being the dominant factor. These findings emphasize the importance of attractive promotional strategies, a strong digital lifestyle, and reliable data security to increase Generation Z's interest in using digital wallets in the modern financial era.